Penerapan Lean Hospital sebagai Upaya Peningkatan Pelayanan Gawat Darurat dalam Cakupan Global - Putri Aulia Rosmayani; Natasya Nazla Prasetyo; Adjrina Dawina Putri; Acim Heri Iswanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
The emergency service unit often has a buildup of patients, which affects services and causes a temporary waiting area for hospitalized patients. The foundation for emergency services is stated in Permenkes 47/2018 with the aim of improving the quality of emergency services that are integrated and integrated in the emergency management system. The purpose of this study is to analyze the application of lean hospital as an effort to improve emergency services in hospitals in a global scope. This research used a literature study method with literature searches, namely Google Scholar and Pubmed, which were selected between 2018-2022. The results of this study were obtained from six research articles related to lean hospital in emergency services that fit the inclusion criteria and keywords. This study shows that lean hospital has a positive influence on the speed of emergency department service time. The reduced time required to provide services can improve the positive image of the hospital. The conclusion of this study is that the implementation of lean hospital can affect waste in waiting time and is most frequent and sensitive. Excessive waiting time can lead to dissatisfaction and a poor view of the hospital by patients or their families.